Copyright and Library Materials for the Handicapped : a Study Prepared for the International Federation of Library Associations and Institutions. - Hébert, Françoise (Walter de Gruyter GmbH, 2017)
The International Federation of Library Associations and Institutions (IFLA) is the leading international body representing the interests of library and information services and their users. It is the global voice of the information profession. The series IFLA Publications deals with many of the means through which libraries, information centres, and information professionals worldwide can formulate their goals, exert their influence as a group, protect their interests, and find solutions to global problems.
Keywords: Fair use (Copyright); Photocopying -- Fair use (Copyright); People with disabilities -- Legal status, laws, etc.; Libraries and people with disabilities.; People with disabilities -- Services for.; Photocopie -- Usage loyal.; Bibliothèques et personnes handicapées.; Personnes handicapées -- Services.; LAW -- Administrative Law & Regulatory Practice.; Libraries and people with disabilities; People with disabilities -- Services for